Land-use and socioeconomic changes related to armed conflicts: A Colombian regional case study. Issue 97 (July 2019) - Garcia Corrales, Lina Maria; Avila, Humberto; Gutierrez, Ronald R.
Highlights: Interrelationship between land cover and economic activities such as agriculture, livestock, and logging can be explained. A strong association between armed conflict and land use change is suggested, as well as between livestock and employment. As municipalities face different socioeconomic and geo-environmental conditions, they will deal with different challenges. Abstract: Colombia has endured one of the longest armed conflicts in the world, influencing land use, local economies, and the environment. The Department of Córdoba, which is part of the Colombian Caribbean region, was a setting of territorial disputes between illegal armed groups. Recently, peace agreements have been reached, thereby leading to a post-conflict period in which conflict-driven socioeconomic and environmental conditions need to be addressed. We used geoenvironmental satellite information and census data to describe land-use evolution in the Department of Córdoba. Our results explain relationships between socioeconomic and geographic variables by using two factors, namely: (1) natural land cover and armed conflict, and (2) pastures and livestock. Five clusters comprised of smaller Colombian territorial units were obtained, exhibiting challenges of environmental governance, conservation of protected areas, and sustainable livestock and agricultural practices. This information provides critical input for institutional decisions during the current post-conflict period.